Needs Assessment Effective educational management of General Buddhist Schools Area 7 - Techathammo, Phrakhruwinaithon Worawuth; Vatasatdho, Phrapalad Honda (Journal of Buddhist Education and Research (JBER), 2024)
This research aims to study the current situation, desired situation and necessary needs, assess the effective educational management strategies of the Buddhist Studies School, General Education Department, Area 7. The research methodology used was a combination of quantitative and qualitative research. The research instruments included a questionnaire and an assessment form for suitability, feasibility, and usefulness. Quantitative research, the sample group consisted of 174 school administrators and teachers. The statistics used were mean, standard deviation, frequency, and percentage. The research results found that current conditions, desired conditions and the necessity for effective educational management of the Buddhist Studies School, General Education Department, Area 7, had an average value of desired conditions higher than the current conditions in every aspect and every issue, with the overall level being at the highest level. When ranked according to the importance of urgent needs that need to be developed first, which is considered from the PNI value as follows: 1) personnel satisfaction 2) learning organization 3) Academic achievement 4) Atmosphere and environment 5) Student characteristics 6) School adjustment and development.